Aesthetic-functional passive Kwawu: Remix of an open-source transradial upper limb prosthesis manufactured by 3D printing (Human Factors in Design, 2023)
Open-source upper limb prostheses manufactured through 3D printing are predominantly active models, limited in both functionality and aesthetics. The objective of this study was to describe the development process of a functional-aesthetic passive upper limb prosthesis remix. The study involved adapting open-source components, parameterized based on anthropometric measurements from a mannequin. The remix of components enabled a device with swift interchangeability between aesthetic and functional terminals. Terminal interchangeability converged functionality and aesthetics in an upper limb prosthesis, thereby bridging the gap in the realm of passive open-source prostheses.
Keywords: prothesis; passive; open-source